Tamara THE ROLE OF DIGITAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES: THE ROLE OF DIGITAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Kavilova, Tamara (Журнал иностранных языков и лингвистики, 2022)
In this article we are talking about the fact that the wide distribution of the distance form of education is possible only when solving a number of complex problems of an economic, technological and psychological nature. Distance learning in our country has not yet found wide application, although today distance learning is considered one of the most effective and promising forms of education throughout the world. At the moment, this term is on everyone's lips, and they are trying to designate all possible ways and forms of using information and computer technologies in the educational process - from the website of an educational institution with brief information about admission to the usual linear textbook published online. The expediency of developing a system of distance education is no longer in doubt and is confirmed by numerous data and assessments of experts in this field, real examples of the introduction of new forms of education in higher and secondary schools.